Technical and Resource Use Efficiency of Urban Vegetable Farming in the Kumasi Metropolis: A Stochastic Frontier Approach - Abdulai, Adams; Fialor, Simon Cudjoe; Bakang, John Eudes Andivi; Jumpah, Emmanuel Tetteh (Asian Journal of Agriculture and Rural Development, 2018)
The changing food demands by the teeming urban population, job search, and sector profitability have made vegetable production indispensable as it contributes to increased incomes and livelihoods of urban dwellers.This study investigated the current level of productive efficiency (technical and allocative) of vegetable farmers in the Kumasi Metropolis using cross-sectional data obtained from 135 sampled farmers using a semi-structured questionnaire. Data analysis was conducted using the stochastic frontier approach to estimate firm-specific technical efficiencies and the factors that influence efficiency levels. The results show that inefficiency exists among the sampled vegetable farmers as they currently achieve an average technical efficiency score of 66.7%. Allocative efficiency estimates for land and labour revealed that both factors of production are over utilised by farmers. The age of the farmer is the main socio-economic determinant of technical efficiency.The study recommends that farmers be educated on the correct use of inputs by extension agents. The government policy of recruiting community extension agents under the ‘planting for food and jobs’ programme is in line with addressing inefficiency in the production sector and should be promoted.